Characterization of Erg K+ Channels in α- and β-Cells of Mouse and Human Islets - Hardy, Alexandre B.; Fox, Jocelyn E.Manning; Giglou, Pejman Raeisi; Wijesekara, Nadeeja; Bhattacharjee, Alpana; Sultan, Sobia; Gyulkhandanyan, Armen V.; Gaisano, Herbert Y.; MacDonald, Patrick E.; Wheeler, Michael B. (The Journal of biological chemistry, 2009)
Voltage-gated eag-related gene (Erg) K+ channels regulate the electrical activity of many cell types. Data regarding Erg channel expression and function in electrically excitable glucagon and insulin producing cells of the pancreas is limited. In the present study Erg1 mRNA and protein were shown to be highly expressed in human and mouse islets and in α-TC6 and Min6 cells α- and β-cell lines, respectively. Whole cell patch clamp recordings demonstrated the functional expression of Erg1 in α- and β-cells, with rBeKm1, an Erg1 antagonist, blocking inward tail currents elicited by a double pulse protocol. Additionally, a small interference RNA approach targeting the kcnh2 gene (Erg1) induced a significant decrease of Erg1 inward tail current in Min6 cells. To investigate further the role of Erg channels in mouse and human islets, ratiometric Fura-2 AM Ca2+-imaging experiments were performed on isolated α- and β-cells. Blocking Erg channels with rBeKm1 induced a transient cytoplasmic Ca2+ increase in both α- and β-cells. This resulted in an increased glucose-dependent insulin secretion, but conversely impaired glucagon secretion under low glucose conditions. Together, these data present Erg1 channels as new mediators of α- and β-cell repolarization. However, antagonism of Erg1 has divergent effects in these cells; to augment glucose-dependent insulin secretion and inhibit low glucose stimulated glucagon secretion.